Recommendations of the Polish Group of Experts for HCV for the treatment of hepatitis C in 2023 - Tomasiewicz, Krzysztof; Flisiak, Robert; Jaroszewicz, Jerzy; Małkowski, Piotr; Pawłowska, Małgorzata; Piekarska, Anna; Simon, Krzysztof; Zarębska-Michaluk, Dorota (Clinical and Experimental Hepatology, 2023)
The recommendations define the principles of diagnosis and treatment of hepatitis C virus (HCV) infection according to the latest knowledge. The main goal of the treatment of HCV infection is to eliminate the virus from the body, which in turn leads to stopping the progression or causes the regression of previously formed changes in the liver. The current version of the guidelines prioritizes pangenotypic regimens and includes guidelines for special patient populations such as children, patients with cirrhosis, human immunodeficiency virus (HIV) and hepatitis B virus (HBV) infection, patients with renal failure, liver failure and lack of response to previous therapies as well as patients in the peri-transplant period.